2022
DOI: 10.1155/2022/1507690
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Assistants Construct Oxidative Stress-Related Gene Signature and Discover Potential Therapy Targets for Acute Myeloid Leukemia

Abstract: Background. Oxidative stress (OS) is associated with the development of acute myeloid leukemia (AML). However, there is lack of relevant research to confirm that OS-related genes can guide patients in risk stratification and predict their survival probability. Method. First, we Data from three public databases, respectively. Then, we use batch univariate Cox regression and machine learning to select important characteristic genes; next, we build the model and use receiver operating characteristic curve (ROC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress (26). In recent years, some studies focused on constructing oxidative stress or ferroptosis-related risk models for predicting patient survival and immune landscapes in various types of malignant tumors (27)(28)(29)(30)(31). However, few risk models were developed based on a combination of these two phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the effects of nanomedicine in targeting ferroptosis and apoptosis can be enhanced by oxidative stress (26). In recent years, some studies focused on constructing oxidative stress or ferroptosis-related risk models for predicting patient survival and immune landscapes in various types of malignant tumors (27)(28)(29)(30)(31). However, few risk models were developed based on a combination of these two phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that PLA2G4A (placental phospholipase A24A is involved in the biological procedure of stress response in various diseases (Brien et al, 2017;Zhang et al, 2018;Mishra et al, 2022). PLA2G4A is overexpressed in different solid cancers such as hepatocellular carcinoma (Fu et al, 2017), prostate cancer (Patel et al, 2008), breast cancer (Chen et al, 2017), cervical cancer (Xu et al, 2019), as well as malignant hematologic diseases, such as AML (acute myeloid leukemia) (Runarsson et al, 2007;Bai et al, 2020;Zhang et al, 2022) In multiple myeloma patients, expression of the PLA2G4A was higher compared to healthy individuals and high gene expression of PLA2G4A is associated with adverse outcomes Frontiers in Genetics frontiersin.org (Mahammad et al, 2021). A previous study showed that FOXO1 (Forkhead Box O1) activation could inhibit the tumor growth and induce cell autophagy and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous advancement of information technology and biotechnology has yielded substantial biomarker data for TCM investigations using machine learning. Zhang [ 89 ] used RF and least absolute shrinkage and selection operator (LASSO) regression to identify important characteristic genes of oxidative stress. The receiver operating characteristic results demonstrated that the model was better in prediction efficiency with an AUC of 0.873.…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%